Assessing the Impact of a Graduated Response Approach for Youth in the Maryland Juvenile Justice System, 2013-2017 - Farrell, Jill L. ([Verlag nicht ermittelbar], 2020)
The Accountability and Incentives Management (AIM) system is a graduated response system that was implemented by the Maryland Department of Juvenile Services (DJS) to promote supervision compliance and reduce rates of supervision violations and recidivism, among other juvenile justice-related outcomes. The purpose of this study was to assess AIM's implementation and outcomes. The treatment group (or AIM group) included adjudicated youths who started/completed probation or aftercare supervision with DJS between November 1, 2015 and October 30, 2017. A comparison group was comprised of youth who were supervised prior to AIM implementation (July 1, 2013 to June 30, 2015). Data were gathered from de-identified administrative records provided by DJS. The unit of analysis is the individual. Variables include: youth delinquency history before supervision; risk/needs assessment; detentions, complaints, and arrests during supervision; AIM sanctions and incentives; youth responses in the AIM program; and demographic characteristics such as age, gender, and race/ethnicity.